Son Tunç/Erken Demir Çağı Van Bölgesi Kronolojisi. Kökeni Aranan Bir Devlet: Urartu - Sevin, Veli
Chronology for the Van Area During the Late Bronze and Early Iron Ages: Urartu, a Search for the Origins of this State; S. 591: engl. Resümee.